Higher order fluctuations of strangeness and flavour hierarchy. (March 2015) - Sarti, V Mantovani; Alba, P; Alberico, W; Bellwied, R; Bluhm, M; Nahrgang, M; Ratti, C
Abstract: We present a preliminary analysis on the sensitivity to the chemical freeze-out temperature of higher order moments of strange particle multiplicity distributions in heavy ion collisions. Within the Hadron Resonance Gas (HRG) model we evaluate ratios of cumulants for kaons ( K ± ) and hyperons (Λ, Σ ±, Ξ −, 0, Ω − ) as a function of the temperature and compare them to the sensitivity profiles obtained from ratios of particle yields. We show that ratios of higher order fluctuations of strange baryons could provide a useful tool to extract the range of freeze-out temperature, once experimental data are available. Finally, a connection to lattice data through the fourth to second cumulant ratio is made. The deconfinement transition on the lattice seems to indicate the possibility of a flavour hierarchy, namely strange quarks seem to deconfine at a higher temperature. We would like to test the possibility for the same scenario to occur at the chemical freeze-out and we show how the inclusion of multi-strange baryons in the evaluation of higher order cumulants might provide a sensitive observable to extract the freeze-out temperature.